Gendered Criminality and Punishment: Does Gender Influence Juvenile Offending and Punishment in Saudi Arabia? - Pryce, Daniel (Crime & delinquency, 2025)
In this paper, we examine the connection between gendered criminality and punishment in Saudi Arabia. Specifically, we examine how the presence of a criminal associate, type of criminal associate, prior criminality, type of court, and number of presiding judges affect what types of punishments are meted out to juvenile male and female offenders. Using a sample of 437 court cases drawn from several court systems, we found that males were more likely to commit substance use-related crimes, whereas females were more likely to commit the offenses of adultery and fornication. We also found that males were more likely than females to engage in kidnapping, a relatively violent crime. In addition, our findings reveal that juvenile males tended to commit crimes with both juvenile and adult associates, whereas juvenile females were more likely to have only adult criminal associates. Also, males were more likely than females to commit murder than substance use-related crimes if they had criminal associates. Lastly, male offenders whose cases were adjudicated by two or more judges were far more likely than male offenders whose cases were tried by a single judge to receive longer prison sentences. Interestingly, we did not find an association between punishment type and gender. The implications of our findings for the juvenile justice system, policy, and future research are discussed.